2005
DOI: 10.1093/bioinformatics/bti680
|View full text |Cite
|
Sign up to set email alerts
|

RSIR: regularized sliced inverse regression for motif discovery

Abstract: Matlab programs are available upon request from the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 26 publications
1
76
0
Order By: Relevance
“…In addition, a few novel interactions are also detected. As ChIP-chip data tends to be noisy, integration of gene expression data to our analysis would be more comprehensive (Sun et al, 2006;Zhong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few novel interactions are also detected. As ChIP-chip data tends to be noisy, integration of gene expression data to our analysis would be more comprehensive (Sun et al, 2006;Zhong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are many different approaches to regularize SIR [6][7][8]. In this work a very simple and intuitive approach is used.…”
Section: Regularized Sliced Inverse Regressionmentioning
confidence: 99%
“…Although results obtained in Reference [4] were satisfactory, in this paper the authors further study other multivariate calibration methods in order to obtain a better prediction performance. A new calibration model based on regularized slice inverse regression (RSIR) [5][6][7][8] is proposed. This model improved the results obtained from both PLS and the popular Support vector regression (SVR) [9], commonly used nowadays.…”
Section: Introductionmentioning
confidence: 99%
“…Tadesse et al (2004) later presented a Bayesian version of a similar approach. To alleviate the dependence of the linearity and Gaussian assumptions, Das et al (2004) suggested an approach using MARS, and Zhong et al (2005) designed a modified slice inverse regression approach, which also effectively reduces the dimensionality without assuming linearity.…”
Section: Joint Analysis Of Sequence Motifs and Expression Microarraysmentioning
confidence: 99%
“…In the past two decades, we have witnessed the development of the likelihood approach to pairwise sequence alignments (Bishop and Thompson, 1986;Thorne et al, 1991); probabilistic models for RNA secondary structure predictions (Zuker, 1989;Lowe and Eddy, 1997;Ding and Lawrence, 2001;Pedersen et al, 2004); the expectation-maximization (EM) algorithm for finding regulatory binding motifs (Lawrence and Reilly, 1990;Cardon and Stormo, 1992), the Gibbs sampling strategies for detecting subtle sequence similarities (Lawrence et al, 1993;Liu, 1994;Neuwald et al, 1997); the hidden Markov models (HMMs) for DNA composition analysis, multiple sequence alignments, gene prediction, and protein secondary structure prediction (Churchill, 1989;Krogh et al, 1994a;Baldi et al, 1994;Burge and Karlin, 1997;Schmidler et al, 2000; Chapters 4 and 5); regression and Bayesian network approaches to gene regulation networks (Bussemaker et al, 2001;Segal et al, 2003;Conlon et al, 2003;Beer and Tavazoie, 2004;Zhong et al, 2005); and many statistical-model based approaches to gene expression microarray analyses (Li and Wong, 2001;Lu et al, 2004;Speed, 2003). All these developments show that algorithms resulting from statistical modeling efforts constitute a significant portion of today's bioinformatics toolbox.…”
Section: Introductionmentioning
confidence: 99%